Penerapan Media Pembelajaran untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Salsabila Hasan; Oktavia Nusi; Susana Daito; Pupung Puspa Ardini; Gustin Lihawa; Astria Maili; Amelia Kadir (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The ability to recognize colors is one of the cognitive development aspects that should be stimulated from an early age. Color recognition helps children develop the ability to classify objects, think logically, improve memory, and better understand their surrounding environment. One strategy that can be used to stimulate this ability is through educational games that are engaging and appropriate for children's developmental characteristics. The